The formation of the black hole in the X-ray binary system V404 Cyg - Miller-Jones, James; Jonker, P.; Nelemans, G.; Portegies Zwart, S.; Dhawan, V.; Brisken, W.; Gallo, E.; Rupen, M. (Wiley-Blackwell Publishing Ltd., 2009)
Using new and archival radio data, we have measured the proper motion of the black hole X-ray binary V404 Cyg to be 9.2 ± 0.3 mas yr-1. Combined with the systemic radial velocity from the literature, we derive the full three-dimensional heliocentric space velocity of the system, which we use to calculate a peculiar velocity in the range 47–102 km s-1, with a best-fitting value of 64 km s-1. We consider possible explanations for the observed peculiar velocity and find that the black hole cannot have formed via direct collapse. A natal supernova is required, in which either significant mass (~11 M?) was lost, giving rise to a symmetric Blaauw kick of up to ~65 km s-1, or, more probably, asymmetries in the supernova led to an additional kick out of the orbital plane of the binary system. In the case of a purely symmetric kick, the black hole must have been formed with a mass ~9 M?, since when it has accreted 0.5–1.5 M? from its companion.